TEACHING SPEAKING THROUGH THINK PAIR SHARE TECHNIQUE - Dini Andriani (Journal of English Education Program (JEEP), 2016)
This paper reports on the implementation of “think pair share technique” in teaching speaking. Twenty two students at seventh grade of MTsN Buniseuri, were taken as the sample of this study. The study employed a qualitative research design. The data were obtained from several instruments, including classroom observation, questionnaires to the students and interview to the teacher. The result of the data from classroom observation and interview showed that the teacher used “think pair share technique” in teaching speaking, as suggested by Lyman (1978). Afterward, the result of the data from questionnaires showed that after the teacher taught by using think pair share technique, the students felt confidence during learning process. It can be seen when they did not prefer to sit at the back of the class in English lesson. The Students’ self-confidence during learning process can be seen also when the students did not worry about making mistake when they speak. Besides most of the students felt that English lesson was fun. It can be concluded that think pair share technique has significant effect on students’ self-confidence. Based on the result of study it is recommended that Think-Pair-Share technique can be used in teaching speaking since it can stimulate the students’ self-confidence in learning speaking and it can create fun and enjoy atmosphere in the classroom.